Sholawat Musawah: The Concept Of Equality Between A Good Life (Hayatan Thayyibah) And A Fair Life (Hayatan Adilah) - Eni Zulfa Hidayah; Devi Suci Windariyah; Maulida Dwi Agustiningsih; Muhammad Masruri (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
Shalawat Musawah, known as gender sholawat, is a prayer often sung by the Nahdhatul Ulama fatayat. The lyrics of sholawat Musawah are by the spirit brought by the Fatayat Nahdhatul Ulama community (NU), rising from oppression to build the independence of the people. This study used descriptive qualitative with the sociology of literature approach. Data analysis was carried out using analytic techniques. This study aims to explain (1) the text and meaning of sholawat Musawah. (2) the intrinsic factor of sholawat Musawah, and (3) the correlation between the author and Shalawat Musawah. The result found that the text and meaning of Shalawat Musawah are related to the theme and perspective of the author, equality theory under Islamic law. Sholawat Musawah consists of 5 intrinsic elements: theme, diction, tone, rhyme, and message. Meanwhile, the relationship between the author and literary works is correlated to the time, place, and author’s standpoint. The lyrics and meanings of Shalawat reflect the author’s thoughts who try to instill the concept of equality to have a good life (hayatan thayyibah) and a fair life (hayatan adilah) through a song (Shalawat).